Auricular Acupressure untuk Mengatasi Xerostomia pada Pasien Hemodialisis: Literatur Review - Risyda Zakiyah Hanim; Lestari Sukmarini (FORIKES, 2022)
Xerostomia is one of the most common complaints, accounting for 78% of hemodialysis patients. The condition of xerostomia causes hemodialysis patients to feel thirsty and creates a strong desire to drink more water. One therapy to reduce xerostomia is auricular acupressure. This study aims to review and discuss studies related to auricular acupressure in hemodialysis patients. The method used was a systematic review. The sources used were from Scopus, Science Direct, PubMed, ProQuest, Ebscohost and Sage published from 2005 to 2021. The keywords in the search were